Physicochemical, interfacial and emulsifying properties of a non-conventional exudate gum (Prosopis alba) in comparison with gum arabic - Vasile, Franco Emanuel (2016)
Physicochemical and emulsifying properties of a novel exudate gum from Prosopis alba (G) were assessed in comparison with the well-known arabic gum (GA). Compositional analysis, intrinsic viscosity and structural characterization as well as gum emulsifying properties (evaluated in terms of mean droplet size distribution of o/w emulsions, ζ-potential, polidispersity and creaming indexes), were performed and related to the dynamic interfacial tension and rheological behavior of the films formed at oil/water interface. Both gums closely resemble in composition with carbohydrates representing the higher fraction (62 and 65% d.b. for G and GA, respectively). The major difference was observed in the protein content which was higher in P. alba gum and largely explains its better interfacial properties. FTIR analysis further supported that the gums share essentially a similar chemical nature. P. alba gum was able to stabilize emulsions better than GA based on its lower droplet size distributions, higher ζ-potential, higher interfacial film elasticity and lower values of the polidispersity and creaming indexes during storage. Furthermore, the formation of stronger viscoelastic films at the oil/water interface as well as the charge distribution of the adsorbed G fractions could contribute to understand the higher stability of G emulsions. Present results provide the first approach to the composition of P. alba gum and evidence its similar or even better emulsifying properties than GA.